Physical/mechanical and antibacterial properties of composite resin modified with selenium nanoparticles - Sara Khaled ElSheikh; El-Sayed Gad Eid; A. M. Abdelghany; Dina Abdelaziz (BMC, 2024)
Abstract Background Accumulation of biofilm over composite resin restorations is one of the principal causes of recurrent caries. Therefore, this study aimed to develop antibacterial composite resins by crystalline selenium nanoparticles (SeNPs), assessing the antibacterial, mechanical, and physical properties of the composite resin after SeNPs incorporation. Methods SeNPs were synthesized via a green method. The nanoparticles were characterized by UV-Vis spectroscopy, fourier transform infrared (FT-IR) spectroscopy and transmission electron microscopy (TEM). The nano-filled composite (Filtek™ Z350XT ) was considered as a control group (G0). Two concentrations of SeNPs (0.005 wt% and 0.01 wt%.) were added to the tested resin composite (G1& G2), respectively. The physical/mechanical and antibacterial properties of the composite specimens (n = 10/group) were characterized. A one-way ANOVA was conducted to analyze these data followed by Bonferroni post hoc test for pairwise comparison. Results Modified composites with SeNPs showed antibacterial activity against E. coli and S. mutans. Mechanical properties including diametral tensile strength, compressive strength, or surface roughness were not affected by nano-incorporation compared to control. Furthermore, the degree of conversion showed no statistical difference. However, SeNPs incorporation into resin composite produces color change that can be visually perceived. Conclusions The green synthesized SeNPs significantly improved the antimicrobial properties of the dental composite without compromising mechanical performance. However, it shows color change after SeNPs incorporation.